Long-term follow-up of the randomized trial of mesorectal excision with or without lateral lymph node dissection in rectal cancer (JCOG0212). Issue 5 (12th March 2020) - Tsukamoto, S; Fujita, S; Ota, M; Mizusawa, J; Shida, D; Kanemitsu, Y; Ito, M; Shiomi, A; Komori, K; Ohue, M; Akazai, Y; Shiozawa, M; et al.
Abstract: Background: Japan Clinical Oncology Group (JCOG) 0212 (ClinicalTrials.gov NCT00190541) was a non-inferiority phase III trial of patients with clinical stage II–III rectal cancer without lateral pelvic lymph node enlargement. The trial compared mesorectal excision (ME) with ME and lateral lymph node dissection (LLND), with a primary endpoint of recurrence-free survival (RFS). The planned primary analysis at 5 years failed to confirm the non-inferiority of ME alone compared with ME and LLND. The present study aimed to compare ME alone and ME with LLND using long-term follow-up data from JCOG0212. Methods: Patients with clinical stage II–III rectal cancer below the peritoneal reflection and no lateral pelvic lymph node enlargement were included in this study. After surgeons confirmed R0 resection by ME, patients were randomized to receive ME alone or ME with LLND. The primary endpoint was RFS. Results: A total of 701 patients from 33 institutions were assigned to ME with LLND (351) or ME alone (350) between June 2003 and August 2010. The 7-year RFS rate was 71.1 per cent for ME with LLND and 70·7 per cent for ME alone (hazard ratio (HR) 1·09, 95 per cent c.i. 0·84 to 1·42; non-inferiority P = 0·064). Subgroup analysis showed improved RFS among patients with clinical stage III disease who underwent ME with LLND compared with ME alone (HR 1·49, 1·02 to 2·17). Conclusion: Long-term follow-up data did not support the non-inferiority of ME alone compared with ME and LLND. ME with LLND is recommended for patients with clinical stage III disease, whereas LLND could be omitted in those with clinical stage II tumours. Graphical Abstract: Long-term follow-up data did not support the non-inferiority of mesorectal excision (ME) alone compared with ME and lateral lymph node dissection (LLND). ME with LLND is recommended for clinical stage III disease, whereas LLND could be omitted for patients with clinical stage II tumours. Selective lateral lymph node dissection supported